2018
DOI: 10.1038/s41565-018-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

High-flux water desalination with interfacial salt sieving effect in nanoporous carbon composite membranes

Abstract: Freshwater flux and energy consumption are two important benchmarks for the membrane desalination process. Here, we show that nanoporous carbon composite membranes, which comprise a layer of porous carbon fibre structures grown on a porous ceramic substrate, can exhibit 100% desalination and a freshwater flux that is 3-20 times higher than existing polymeric membranes. Thermal accounting experiments demonstrated that the carbon composite membrane saved over 80% of the latent heat consumption. Theoretical calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(108 citation statements)
references
References 58 publications
4
104
0
Order By: Relevance
“…[ 1 ] Nanomaterial‐based technologies, capable of effectively and affordably extracting potable water from unconventional water sources (such as, salt water, industrial waste water, and rain water), make critical contribution for sustainable water use. [ 2–5 ] Particularly, 2D‐material‐based nanofluidic membranes are considered as promising materials for next‐generation water desalination and purification. [ 6 ] For example, monolayer graphene with sub‐nanometer pores exhibits nearly 100% salt rejection and high water permeability, [ 7,8 ] with orders of magnitude greater than commercial reverse osmosis (RO) membranes (≈2 Lm −2 h −1 bar −1 ).…”
Section: Figurementioning
confidence: 99%
“…[ 1 ] Nanomaterial‐based technologies, capable of effectively and affordably extracting potable water from unconventional water sources (such as, salt water, industrial waste water, and rain water), make critical contribution for sustainable water use. [ 2–5 ] Particularly, 2D‐material‐based nanofluidic membranes are considered as promising materials for next‐generation water desalination and purification. [ 6 ] For example, monolayer graphene with sub‐nanometer pores exhibits nearly 100% salt rejection and high water permeability, [ 7,8 ] with orders of magnitude greater than commercial reverse osmosis (RO) membranes (≈2 Lm −2 h −1 bar −1 ).…”
Section: Figurementioning
confidence: 99%
“…Majumder et al [11] reported a flow rate of four to five orders of magnitude faster than conventional fluid flow through channels of 7 nm diameter in micro-fabricated membranes where aligned carbon nanotubes (CNTs) served as pores. [13] To achieve highly selective ion transmembrane transport, the microstructure of porous materials was optimized constantly. [12] On the other hand, ion selectivity of nanoporous materials has been revealed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater desalination is a very promising means to gain fresh water . Osmosis membrane technology, solar desalination technology, and some other technologies have been used for desalination. Among them, efficient water evaporation technique has attracted tremendous attention due to its distinct advantages, such as inexhaustibility, safety, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%